Evaluasi dan Perkembangan Ketahanan Pangan Indonesia Tahun 2023–2025 berdasarkan Kerangka Empat Pilar FAO - Nabilah Zahra Tiftazani; Muhammad Rifkie Sabitul Noerzaman; Cika Gracella Hermawan; Nada Askori; Maulidia Iftitakhur Rohmah; Andi Setiawan (Jurnal Riset Multidisiplin Edukasi, 2025)
Food security is a critical and crucial issue for Indonesia, facing multidimensional challenges such as climate change, import dependence, and inequality in distribution processes. This study aims to evaluate the development of Indonesia's food security between 2023 and 2025 using the FAO's four pillars framework (Availability, Accessibility, Utilization, and Stability). The research method used is descriptive qualitative, utilizing secondary data from various government reports and international institutions. The research results show that Indonesia's food security is in a state of "unstable recovery." There has been progress in the utilization pillar, as evidenced by a decrease in stunting prevalence and improvements in food production by 2025. However, food security remains under pressure due to structural vulnerabilities in the pillars of availability (dependence on imports and production fluctuations), accessibility (unequal distribution and limited purchasing power), and stability (climate impacts and global price fluctuations). It is concluded that despite progress, Indonesia's food security is not yet fully robust. Integrated policies focused on production diversification, distribution reform, strengthening food reserves, and accelerating nutritional improvements are needed to build more resilient food security.